Selenium analysis by an integrated microwave digestion-needle trap device with hydride sorption on carbon nanotubes and electrothermal atomic absorption spectrometry determination - Maratta Martínez, Sergio Ariel (2018)
An integrated microwave assisted digestion (MW-AD) – needle trap device (NTD) for selenium determination in grape pomace samples is presented. The NTD was filled with oxidized multiwall carbon nanotubes (oxMWCNTS) where Se hydrides were preconcentrated. Determination was carried out by flow injection-electrothermal atomic absorption spectrometry (FI-ETAAS). The variables affecting the system were established by a multivariate design (Plackett Burman), indicating that the following variables significantly affect the system: sample amount, HNO3 digestion solution concentration, NaBH4 volume and elution volume. A Box-Behnken design was implemented to determine the optimized values of these variables. The system improved Se atomization in the graphite furnace, since only trapped hydrides reached the graphite furnace, and the pyrolysis stage was eliminated according to the aqueous matrix of the eluate. Under optimized conditions the system reached a limit of quantification of 0.11 μg kg− 1, a detection limit of 0.032 μg kg− 1, a relative standard deviation of 4% and a preconcentration factor (PF) of 100, reaching a throughput sample of 5 samples per hour. Sample analysis show Se concentrations between 0.34 ± 0.03 μg kg− 1 to 0.48 ± 0.03 μg kg− 1 in grape pomace. This system provides minimal reagents and sample consumption, eliminates discontinuous stages between samples processing reaching a simpler and faster Se analysis.